An integrated vision of history Chronicle of the visit of Raúl Porras Barrenechea to Chile - Pinto-Bazurco Mendoza, Ricardo (2018)
History as a tool of integration and conciliation is effective for the development of the people and even more so when their stories have gone through swings. In this sense, the presence of Raúl Porras Barrenechea in Santiago, Chile, during the celebration of the symposium in homage to the centenary of the birth of José Toribio Medina, is a precursor and visionary event. For his contribution to the heuristic of Chilean historiography, with unpublished documentation, and his show of gratitude and recognition to the work of who he considered one of the most important historians constituted the main axis of his discourse, converting, in this way, the History in an integrating element between Peru and Chile. This «spiritual and historical» community, present in the life of both peoples, was what led Medina, says Porras, to see Peru as a «historical fraternal entity» and that Porras reaffirms when considering a symbiosis between both countries whose history it nourishes and enriches, constantly. A fact that is reaffirmed, historically, with characters such as Pedro de Oña or Bernardo O’Higgins and that Raúl Porras Barrenechea delineated, masterfully, in those days of October 1952.